Penggunaan ATR-FTIR (Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy) pada Kedokteran Gigi - Dede Arsista; Yosi Kusuma Eriwati (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2021)
Characterization of a material in dentistry has been developed for research purposes. One of the characterization tools that are often used in dentistry is Fourier Transform Infrared Spectroscopy (FTIR). Fourier Transform Infrared Spectroscopy (FTIR) is a technique used to obtain the absorbance pattern of a compound of a material. FTIR can be used to analyze organic and inorganic compounds. In addition, FTIR can also be used for qualitative analysis including functional group analysis (the presence of a 'peak' from a specific functional group) along with its pattern and quantitative analysis by looking at the absorption strength of compounds at certain wavelengths. determine the composition of the compounds that make up a material. This paper aims to examine the use of Fourier Transform Infrared Spectroscopy FTIR as a characterization tool in dentistry. The spectral image pattern produced by the ATR-FTIR tool can provide information on the composition of the compound so that it becomes one of the tools of choice for characterizing a material.